PERSEPSI MASYARAKAT TERHADAP PERILAKU PEMASUNGAN ORANG DENGAN GANGGUAN JIWA DI DESA SUNGAI UNGAR UTARA KECAMATAN KUNDUR UTARA - Sarmila; Nanik Rahmawati; Rahma Syafitri (LPPM STISIP Persada Bunda, 2023)
Sungai Ungar Utara Village is an area that is still classified as rural. As compared to its characteristics with other villages, Sungai Ungar Utara Village has many mental disorders. People with mental disorders who are shackled by their families because they often disturb and rage among the local community cause anxiety in the community. This study aims to find out how the community views the shackling behavior of people with mental disorders in Sungai Ungar Utara Village, Kundur Utara District. The method used in this research is a qualitative method using a descriptive approach. The data sources used by researchers are data sources in the form of observations, interviews, documentation. The data obtained through the results of semi-structured interviews. In this study to determine the informants using purposive sampling technique or first determine the criteria of informants. The theory used in this research is. Social Construction Theory by peter L Berger and Luckman. Based on the results of this study, there is social construction in the community in Sungai Ungar Utara Village, which can be seen from the community's view of the shackling behavior of people with mental disorders, some agree or disagree with the deprivation action.